Characteristics of stroke patients: An analytical description of outpatient at the hospital in Semarang Indonesia - Lestari, Lis Mukti; Pudjonarko, Dwi; Handayani, Fitria Handayani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
A country's population characteristic is influenced by differences in lifestyle due to changes in demographics, epidemiology and culture of each region so, the behavior risk is detrimental to health. The purpose of this study is to determine the characteristics of stroke patients in Semarang Districts. The method used was descriptive-analytic and samples were taken using a total sampling technique of 92 patients diagnosed with a stroke. Data obtained from patient medical records and interviews with patients or their families. The patients interviewed had an MMSE score of 24-30. The results of this study showed the characteristics of stroke patients in Semarang 57.6 percent aged 40-59 years, male patients by 50 percent, the population who had never been at school 30.4 percent, non-hemorrhagic stroke 83.7 percent, patients with left hemiparesis 51.1 percent, patients with risk factors for hypertension 85.9 percent, and 79.6 percent of patients had never been exposed to information about stroke. History of diabetes mellitus and smoking habits significantly influences the occurrence of non-hemorrhagic stroke. Patients with diabetes mellitus have a risk of 9.6 times and patients with smoking have a risk of 3.9 times to experience a non-hemorrhagic stroke.Karakteristik pasien stroke: Deskripsi analitis pada pasien rawat jalan di rumah sakit di Semarang IndonesiaAbstrakKarakteristik penduduk suatu negara dipengaruhi oleh perbedaan gaya hidup akibat adanya perubahan demografi, epidemiologi dan juga budaya masing-masing daerah sehingga berisiko terjadinya perilaku yang merugikan kesehatan. Tujuan penelitian ini adalah untuk mengetahui karakteristik pasien stroke di Kabupaten Semarang. Metode yang digunakan adalah deskriptif analitik dan sample diambil dengan menggunakan tehnik total sampling terhadap 92 orang pasien yang di diagnosa stroke. Data diperoleh dari rekam medis pasien dan wawancara kepada pasien atau keluarganya. Pasien yang diwawancara memiliki nilai MMSE 24-30. Hasil penelitian ini menunjukkan karakteristik pasien stroke di Kabupaten Semarang 57,6 persen berusia 40-59 tahun, pasien jenis kelamin laki-laki sebesar 50 persen, penduduk yang tidak pernah sekolah 30,4 persen, stroke non hemorhagik 83,7 persen, pasien dengan hemipharesis kiri 51,1 persen, pasien dengan faktor resiko hipertensi 85,9 persen, dan 79,6 persen pasien belum pernah terpapar informasi tentang stroke. Riwayat diabetes melitus dan kebiasaan merokok berpengaruh secara signifikan untuk terjadinya stroke non hemorhagik. Pasien dengan diabetes melitus memiliki risiko 9,6 kali dan pasien dengan kebiasaan merokok memiliki risiko 3,9 kali untuk mengalami stroke non hemorhagik.